Direct evidence of plant consumption in Neolithic Eastern Sudan from dental calculus analysis - Giusy Capasso; Dulce Neves; Alessandra Sperduti; Emanuela Cristiani; Andrea Manzo (Scientific Reports, 2024)
Abstract The Neolithic communities of Eastern Sudan combined intensive pastoralism with plant exploitation as their main subsistence strategies. However, to date, it remains unclear which plant species were part of the human diet during the Neolithic. This contribution presents direct data on plant consumption in Eastern Sudan from the Early to Late Neolithic, obtained through the analysis of microdebris inclusions in the dental calculus of 37 individuals, integrated by dentoalveolar pathology analysis of 78 individuals, from the sites UA53 (4th millennium BCE) and Mahal Teglinos (3rd–2nd millennium BCE), located in the Gash Delta/Kassala region. Dental calculus inclusions indicate a diverse intake of cereals, legumes, and tubers during the Middle Neolithic, thus supporting the hypothesis of high reliance on plant resources. Dentoalveolar pathologies, possibly related to the consumption of carbohydrate-rich foods, have also been recorded. For the Late Neolithic, consistent with the shift towards aridity that occurred in the Middle/Late Holocene, dental calculus exclusively indicates the exploitation of sorghum and tubers—species well adapted to arid conditions—showing how the Neolithic communities modified their subsistence in response to environmental changes. Evidence of plant processing techniques, such as cooking/heating, was also revealed from the dental calculus analysis.